Sistema de gestión documental para el registro de la propiedad inmobiliaria y mercantil del cantón Latacunga. - Aguiar Jiménez, Paúl Adrián (2019)
The present project attends about the development of a document management system as a determining factor in the handling of documents and files in the Real Estate and Commercial Registry of the Latacunga Canton, the importance of the implementation of the software will allow to reduce the time of search of the information and improvement in the handling of certificates easy access to the data providing availability, reliability, integrity and security in the documents; In order to develop the application, the IterativeIncremental model was used because it was adjusted to the needs of the system. In the analysis, the necessary requirements for the design and coding could be determined. Among the most important requirements are the user management, books and certificates which were applied their respective test cases for each iterations resulting in compliance with the needs of this institution, the tools used in this project were: PHP with Laravel Framework (5.7) that offers the necessary functionalities to develop modern applications easily and safely and the MySQL Database Manager. It was determined that the processes that were carried manually were very delayed, with the implementation of the document management system it was possible to reduce the search time, a better control of the information and integrity of the same allowing obtaining more reliable information in several departments of the entity public.